MAKNA SPIRITUAL IBADAH QURBAN DI MASA PANDEMIC COVID-19 - Muhith Muhammad Ishaq (STAI DI AL-HIKMAH, 2022)
This study analyzes the spiritual meaning of the Qurban worship carried out by Muslims during the Covid-19 Pandemic. This research is a type of qualitative research with literature review. All primary and secondary research data are sourced from libraries, namely the Qur'an, books of interpretation, hadith, journals, and research published online. The data analysis method used is data reduction, data display, and drawing conclusions. The nature of the data analysis used is descriptive analytical. The research finding is that the Qurban worship during the COVID-19 pandemic can be a suggestion to bring people closer to Allah SW. In addition to Allah SWT, worshiping the Qur'an during the COVID-19 pandemic is at the same time bringing it closer to fellow humans, from family, relatives and neighbors. The happiness and joy that resides and springs up in the soul is expected to foster immunity in the face of the existing pandemic, just as the gratitude and patience that occurs in the soul of a believer will protect him, placing him between the two poles of goodness.